Epidemiology of zoonotic tick-borne diseases in Latin America: Are we just seeing the tip of the iceberg? [version 2; peer review: 2 approved, 1 not approved] - Alfonso J. Rodriguez-Morales; D. Katterine Bonilla-Aldana; Samuel E. Idarraga-Bedoya; Juan J. Garcia-Bustos; Jaime A. Cardona-Ospina; Álvaro A. Faccini-Martínez (F1000Research, 2019)
Ticks are responsible for transmission of multiple bacterial, parasitic and viral diseases. Tick-borne diseases (TBDs) occur particularly in tropical and also subtropical areas. The frequency of these TBDs has been increasing and extending to new territories in a significant way, partly since ticks’ populations are highly favored by prevailing factors such as change in land use patterns, and climate change. Therefore, in order to obtain accurate estimates of mortality, premature mortality, and disability associated about TBDs, more molecular and epidemiological studies in different regions of the world, including Latin America, are required. In the case of this region, there is still a limited number of published studies. In addition, there is recently the emergence and discovering of pathogens not reported previously in this region but present in other areas of the world. In this article we discuss some studies and implications about TBDs in Latin America, most of them, zoonotic and with evolving taxonomical issues.